Productivity assessment and its improvement strategies for small metal workshops (Journal of Mechanical Engineering, 2009)
A case study research was conducted with a view to assess the impact of five factors such as man, machine, material, money, and safety on productivity. The scope of this study was limited only to small metal workshops, which produces customized independent products. 18 case studies were performed based on selected workshops of different categories (welding shops, repair shops, sheet metal shops). Total Productivity Model (TPM) has been used as the theoretical base of the research model. It has been identified that insufficiency of skilled workers, improper utilization of materials, inefficient inventory control, ineffective safety package etc., are the most critical obstacles to productivity improvement in terms of product and material and hence to the overall productivity improvement of the organization as a whole. Some productivity improvement strategies made on the basis of the observations and analysis are also included in this paper. Keywords: Assessment, Productivity, Total Productivity Model (TPM), and Small Metal Workshops. doi:10.3329/jme.v39i1.1827 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 8-12